Technological advances in Universal Neonatal Hearing Screening (UNHS). (September 2013) - Hatzopoulos, Stavros; Ciorba, Andrea; Sliwa, Lech; Skarzynski, Piotr
Abstract: This paper presents a review of the major technological contributions in the field of universal neonatal hearing screening, during the last decade. Dedicated sections include references to the following : 1) the role of automated auditory brainstem responses (AABR) in screening; 2) the potential role of Auditory Steady State responses (ASSR) as a substitute of AABR; 3) the assessment of hearing threshold via recordings of distortion product otoacoustic emissions and the limitations of the clinical protocols to a hearing level < than 35dB HL; 4) the integration of multiple assessment protocols in one portable device, to be used in the intervention part of the hearing screening programme.